Seeds of giant dodder (Cuscuta reflexa) as a function of extract procedure and solvent nature - Noureen, S. (Academic Press, 2018)
Seeds of a renowned medicinal plant, giant dodder (Cuscuta reflexa), were assessed to appraise the effect of solvent and extraction technique variation on antioxidants potential. Dodder seed, also called cuscuta seed, has been considered superb tonic in traditional herbal medication for eyes, liver, spleen and kidney. Results show that selected solvent and procedure plays a key role in the composition and activity of extractable material. Three extraction procedures Orbital shaker, Decoction and Ultrasonic assisted extraction and five different solvents n-hexane, ethyl acetate, 100 methanol, 80 methanol and 60 methanol were used to get optimized conditions. Total phenolic and flavonoids content were found maximum in the extracts of aqueous organic system containing 80 methanol in Ultrasonic assisted extraction method but in case of tannins ethyl acetate and Orbital shaker extraction was found more suitable partner. Antioxidant estimation assays showed a little bit variation as DPPH and ABTS exhibited maximum inhibition in 80 methanol and Ultrasonic assisted extraction but 100 methanol was found better for FRAP assay. Decoction results were mostly in between the both Orbital shaker and Ultrasonic assisted extraction. Overall results indicate that coexistence of polar solvents and Ultrasonic assisted extraction gives a better choice for extractability of potent antioxidants from seeds. HPLC analysis confirmed presence of valuable phenolic acids. Pearson's correlation coefficient reveals a significant relationship between extracted components and antioxidant capacity P < 0.05 or 0.01. Â© 2018 Academic Press.